Gender-Differential Association Between Loneliness and Alcohol Consumption: a Pooled Analysis of 17,808 Individuals in the Multi-Cohort GESA Consortium - Johar, Hamimatunnisa; Atasoy, Seryan; Beutel, Manfred; Braehler, Elmar; Schomerus, Georg; Binder, Harald; Peters, Annette; Zöller, Daniela; Fleischer, Toni; Otten, Danielle; Kampling, Hana; Kruse, Johannes; et al. (My University, 2023)
Loneliness is an established risk factor for impaired health. However, the evidence of whether increased alcohol consumption is a coping mechanism to alleviate loneliness for both genders remains sparse. The cross-sectional study included 8898 men and 8910 women (mean age of 56.2 ± 11.5 years) from three population-based cohort studies in Germany (KORA-FF4, GHS, and SHIP. Daily alcohol consumption (g/day) was measured, and risky drinking was identified using gender-specific thresholds (40 g/day for men and 20 g/day for women). Loneliness was assessed by asking if the participants feel lonely. Multivariable regression analyses were employed to examine the association between alcohol use outcomes and loneliness with adjustments for confounders. Women reported feeling lonely more frequently than men (14.8% vs 10.4%). In men, loneliness was positively associated with levels of alcohol consumption (ß = 1.75, SE = 0.76, p = 0.04) and risky drinking (OR = 1.33, 95% CI = 1.07–1.66, p = 0.02) and was even more profound in men with lower educational levels. In women, loneliness was associated with reduced odds of risky consumption (OR = 0.76, 95% CI = 0.60–0.96, p = 0.02) but not with alcohol consumption levels. The findings indicate gender-differential associations of loneliness with increased levels and risky alcohol consumption in men but with decreased risky consumption in women.
Keywords: ddc:610